FORMULATION, DEVELOPMENT AND EVALUATION OF FAST DISSOLVING DRUG. LEVOSALBUTAMOL TABLETS - Aditya Duby; Md Shamimuddin; Mukesh Sharma (Journal of Biomedical and Pharmaceutical Research, 2020)
Asthma symptoms are the result of bronchial hyperresponsiveness, bronchospasm, and chronic airway inflammation. Short-acting, inhaled beta2 agonists; oxygen; intravenous fluids; and corticosteroids are the mainstays of treatment for acute exacerbations. The R-enantiomer of albuterol is responsible for bronchodilation. The S-enantiomer exhibits broncho-constricting activity in vitro, which may be mediated by muscarinic receptors and may be opposed by adding the anticholinergic agent ipratropium bromide. Levalbuterol improves pulmonary function to a greater extent than racemic albuterol and reduces the need for costly hospitalizations in patients with acute asthma exacerbations. It was estimated that more than 339 million people suffer from asthma. Asthma is the most common noncommunicable disease among children. Most deaths occur in older adults. Under Preformulation study, the physicochemical properties were complied with the IP and USP specification. Physical properties such as appearance, melting point, effect of temperature and humidity in different conditions were more in Levosabutamol raw powder. Parameters evaluated were within the USP limit. The compatibility evaluations were performed by FTIR spectroscopy. The observation implies that the drug and polymers were compatible with each other. There were no interaction found between polymers and drug. The formulations were evaluated on the basis of Pharmacopoeial specification visual appearance, pH, drug content, Hardness, Friability, Disintegration test, assessment of drug release, release kinetics were carried out as per specifications and results were found to be complied with the Pharmacopoeial specification.